Towards 5G：heterogeneous cellular network architecture design based on intelligent SDN paradigm - Yifan ZHOU; Zhifeng ZHAO; Honggang ZHANG (Dianxin kexue)
To enrich the SDN（software defined networking）with intelligence and learning capability，an intelligent SDN paradigm was proposed for the first time.Combining it with the traditional cellular networks，5G-oriented heterogeneous cellular network architecture based on the intelligent SDN was set up，which made the integrated management of radio access networks and core networks possible.Based on the management and coordination of intelligent SDN，the decoupling of control and data，decoupling of uplink and downlink，and dynamic resource utilization in radio access networks to improve the spectrum efficiency and energy efficiency were put forward；content caching and network security strategies were deployed in the core networks to enhance the network scalability and data throughput.Globally，the resource utilization in radio access networks and core networks was optimized to achieve the network function virtualization and customized service provision，which contributed to the in-depth combination between the heterogeneous cellular networks and intelligent SDN.